Physics of failure as a technology enabler for electrical machines in transportation: reliability-oriented design of low voltage insulation systems - Madonna, Vincenzo (2020)
In modern electrical machines there is an-ever-increasing push towards high power density and efficiency, which are thus considered as main design objectives. On the other hand, electrical machines used in certain applications, such as in the transport industry, are also required to be highly reliable and robust. In order to achieve the much needed power density performances, “extra” stresses are being experienced by the insulation systems of these machines, often resulting in accelerated components degradation and compromised system-level reliability figures. In general, the lifetime consumption evaluation and the reliability assessment of electrical machines components, including the insulation system, are still evaluated through outdated methods. These are often based on historical data and adopt constant failure rates, derived by statistically post-processing the failure times of a large number of built prototypes. This is of course a very time-consuming and expensive process. In application fields such as automotive and aerospace, the reliability assessment procedures can then negatively affect the development timeline of an electrical product, especially for certification.